Screening, Discovery, and Development of Immune-Instructive Biomaterials for Modulation of Dendritic Cells - Fateh, Shirin (2024)
Biomaterials are increasingly important in healthcare for their potential applications in medical implants, immunotherapies, vaccine development, tissue engineering, organ transplantation, and personalised medicine. However, challenges such as infection and complications at implantation sites necessitate the development of biomaterials that induce appropriate immune responses. While polymer microarrays are effective in biomaterial discovery, they often overlook non-adherent immune cells, secretome profiles, and paracrine signalling, which are critical for comprehensive understanding. Dendritic cells (DCs), as central regulators of the immune system, serve as a relevant model for studying the modulation of immune responses by biomaterials. Various studies have demonstrated that natural and synthetic polymers can influence DC maturation and phenotype, indicating the potential to design biomaterials that modulate adaptive immune responses. Nonetheless, achieving specific biological functions, like anti-inflammatory properties, remains challenging due to an incomplete understanding of material-biological interactions.